Oatmeal is better than no meal: the career pathways of African American male professional athletes from underserved communities in the United States. Issue 4 (4th July 2021) - Book, Robert T.; Henriksen, Kristoffer; Stambulova, Natalia
ABSTRACT: The objective of this study was to explore career pathways to athletic success in American professional athletes with low socioeconomic background. Ten African American professional male athletes, who met the criteria of playing at least one year in a professional league and spending their formative years in an American underserved community, participated in the study. Interviews inspired by the cultural praxis of athletes' careers, lasted 68–137 minutes, and the transcripts were thematically analysed. Four career stages (childhood years, middle/high school years, college years, professional years) and three themes (context, challenges, coping) were visible in the career pathways of the participants. During the first stage, the athletes' athletic foundation was developed by participating in inexpensive, easy to access sports in unstructured sporting environments, while simultaneously relying upon the strength of a mother to keep them safe. An increased susceptibility to the dangers of environmental factors (e.g., drugs, gangs) during the middle/high school years made this period of time the most precarious for the athletes, but was also the most crucial for their athletic development. The college years were a time of "catching up, " whereby the athletes entered a whole new environment for which they were physically (e.g., underweight) and psycho-socially (e.g., racial integration) unprepared, but their hard work and the help of peers and coaches propelled them to success (i.e., professional contract). Finally, the results indicate that coping resources the athletes developed dealing with hardship were perceived as key factors enabling them to endure the difficulties of a professional career.